Novel alkenone-producing strains of genus Isochrysis (Haptophyta) isolated from Canadian saline lakes show temperature sensitivity of alkenones and alkenoates. (July 2018) - Araie, Hiroya; Nakamura, Hideto; Toney, Jaime L.; Haig, Heather A.; Plancq, Julien; Shiratori, Takashi; Leavitt, Peter R.; Seki, Osamu; Ishida, Ken-ichiro; Sawada, Ken; Suzuki, Iwane; Shiraiwa, Yoshihiro
Graphical abstract: Highlights: Novel LCA-producing strains from Canadian lakes established as unialgal cultures. Seven strains were categorized in the Isochrysis clade using genomic analysis. One strain produces C41 and C42 alkenones that are sensitive to temperature changes. New alkenoate-based indices from isolated strains for temperature reconstructions. Abstract: Alkenone-producing species have been recently found in diverse lacustrine environments, albeit with taxonomic information derived indirectly from environmental genomic techniques. In this study, we isolated alkenone-producing algal species from Canadian saline lakes and established unialgal cultures of individual strains to identify their taxonomical and molecular biological characteristics. Water and sediments collected from the lakes were first enriched in artificial seawater medium over a range of salinities (5–40 g/L) to cultivate taxa in vitro. Unialgal cultures of seven haptophyte strains were isolated and categorized in the Isochrysis clade using SSU and LSU rRNA gene analysis. The alkenone distributions within isolated strains were determined to be novel compared with other previously reported alkenone-producing haptophytes. While all strains produced the typical C37 and C38 range of isomers, one strain isolated from Canadian salt lakes also produced novel C41 and C42 alkenones that are temperature sensitive. In addition, we showed that all alkenone unsaturation indices (e.g., U 37 K and U 37 K ′ ) are temperature-dependent in culture experiments, and that alkenoate indices (e.g., U 37 A, U 38 A, RIA38 and A37 /A38 ) provide alternative options for temperature calibration based on these new lacustrine algal strains. Importantly, these indices show temperature dependence in culture experiments at temperatures below 10 °C, where traditional alkenone proxies were not as sensitive. We hypothesize that this suite of calibrations may be used for reconstructions of past water temperature in a broad range of lakes in the Canadian prairies.